Tuneable mesoporous silica material for hydrogen storage application via nano-confined clathrate hydrate construction - Radu-George Ciocarlan; Judit Farrando-Perez; Daniel Arenas-Esteban; Maarten Houlleberghs; Luke L. Daemen; Yongqiang Cheng; Anibal J. Ramirez-Cuesta; Eric Breynaert; Johan Martens; Sara Bals; Joaquin Silvestre-Albero; Pegie Cool (Nature Communications, 2024)
Abstract Safe storage and utilisation of hydrogen is an ongoing area of research, showing potential to enable hydrogen becoming an effective fuel, substituting current carbon-based sources. Hydrogen storage is associated with a high energy cost due to its low density and boiling point, which drives a high price. Clathrates (gas hydrates) are water-based (ice-like) structures incorporating small non-polar compounds such as H2 in cages formed by hydrogen bonded water molecules. Since only water is required to construct the cages, clathrates have been identified as a potential solution for safe storage of hydrogen. In bulk, pure hydrogen clathrate (H2O-H2) only forms in harsh conditions, but confined in nanospaces the properties of water are altered and hydrogen storage at mild pressure and temperature could become possible. Here, specifically a hydrophobic mesoporous silica is proposed as a host material, providing a suitable nano-confinement for ice-like clathrate hydrate. The hybrid silica material shows an important decrease of the pressure required for clathrate formation (approx. 20%) compared to the pure H2O-H2 system. In-situ inelastic neutron scattering (INS) and neutron diffraction (ND) provided unique insights into the interaction of hydrogen with the complex surface of the hybrid material and demonstrated the stability of nano-confined hydrogen clathrate hydrate.